Anosmia and Ageusia in Adult Patient with Covid-19 - Puji Wulandari; Giri Widakdo; Slametiningsih Slametiningsih; Melati Fajarini (Universitas Muhammadiyah Semarang, 2022)
Early detection of COVID-19 disease in the community is essential, one of the ways is by identifying the symptoms of anosmia (loss of sense of smell) and ageusia (loss of sense of taste). However, it is not yet known how the characteristics of these symptoms can be used as a protocol to prevent the spread of the SARS-CoV-2 virus. This study aims to obtain an overview of the prevalence and characteristics of anosmia and ageusia in adult patients with COVID-19 in the community setting. Descriptive research with a retrospective approach was used to collect outpatients’ data at Puskesmas Kecamatan Cempaka Putih from May – June 2021. A total of 105 participants from 400 patients were selected using a simple random sampling with inclusion criteria were patients who confirmed positive for COVID-19 based on the results of the PCR Swab and had symptoms of anosmia and ageusia. Demographic data and general symptoms of COVID-19 were obtained from the Epidemiological Investigation of Suspected COVID-19 form from the Ministry of Health recorded in medical records, Data on prevalence and characteristics of anosmia and age were obtained through a questionnaire consisting of 12 questions made in google form format and distributed via WhatsApp to the participant. Descriptive analysis showed that from a total of 105 patients in the community with anosmia and ageusia, 103 patients (98.1%) reported anosmia, 50 patients (47.6%) had ageusia, and 48 patients (45.7%) experienced both symptoms. Patients experienced anosmia before being diagnosed with COVID-19 (62, 60.2%) and ageusia after being diagnosed with COVID-19 (28, 56.0%). The median duration of anosmia in days (IQR) was 7 (2) and ageusia was 5 (4). Anosmia and ageusia are symptoms experienced by an adult patient with COVID-19 in the community setting. These two symptoms need to be recognised as typical symptoms of COVID-19, added to the early detection of COVID-19, and included in the self-isolation protocol. Further research on the impact of anosmia and age on health and long-term decline in sensory function after COVID-19 needs to be done.